Negotiation strategies of service captive mobility restricted travellers (International Journal of Food and Nutritional Sciences, 2021)
The study investigates the idea of service captivity through the experiences of tourists with mobility impairments (TMDs) who encountered the restrictive tourism services in India, such as increased charges, limited and incomplete services, and a lack of infrastructure for people with disabilities. The TMDs nonetheless made the decision to travel to the nation despite their perceptions of captive services or the power disparity between service providers and customers, where the former frequently puts their revenue ahead of the latter's satisfaction and well-being. Such a consumer mindset led the researchers to investigate the viewpoints of domestic and foreign mobility-disabled tourists on their service captive experiences in the Indian tourism sector in order to comprehend how such experiences influence their travel behavior. The study confirmed the power disparity between service providers and consumers at various identifiable touch points of the servicescape, its causes, and its impacts on their participation in tourism activities through the application of Rayburn et al.'s (2020) service captivity framework, with a few minor deviations. The findings have repercussions for all of the tourism supply chain's participants as well as for policymakers. To fully realize the promise of accessible tourism, it demands for revamping the service landscape and customer interactions.